PENGEMBANGAN MEDIA TERAPI PERBAIKAN RESPIRATORY RATE BERBASIS AUDIO VISUAL BERBASIS ISO 9241-210:2019 HUMAN-CENTERED DESIGN - Khudori, Ahsanunnaseh; Kusuma, Wahyu Teja; Anshori, Mochamad; Yuono, Nugroho Teguh; Wibowo, Heri Wahyu (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The spread of the Covid-19 virus is of more concern to various parties. A referral hospital in Surabaya City noted that from March 2020 to July 2021 the recovery rate was 85% of patients exposed to the Covid-19 virus. More than 425 people are members of TNI soldiers, TNI civil servants, retired officers, and family members exposed to the virus. The handling and prevention of the spread of the Covid-19 virus are still being carried out. This study aims to develop respiratory rate improvement therapy media based on audiovisual media. The method to be used is based on ISO 9241-210:2019 Human-centered design as well as several other methods such as persona and expert validation. This research was conducted by conducting pre-production, production, and then editing scenarios. The results of this study were validated by testing the audio-visual media carried out by informatic validation and physiotherapy experts. The results of the expert validation prove that audiovisual media has succeeded because that has met the needs of the users and has a significant effect on improving the respiratory rate.